On positive operators without invariant sublattices - Çağlar, Mert; Gönülli, Uğur; Mısırlıoğlu, Remzi Tunç; ÇAĞLAR, MERT (My University, 2009)
By slightly modifying some of the examples given in [6], we obtain further examples of positive operators on the discrete Banach lattices c0, c, and `p (1 ≤ p < ∞) without non-trivial closed invariant sublattices.
Keywords: Invariant subspace; positive operator; invariant sublattice